Selection of susceptible and refractory lines of Glossina morsitans centralis for Trypanosoma congolense infection and their susceptibility to different pathogenic Trypanosoma species - Moloo, S.K.; Kabata, J.M.; Waweru, F.; Gooding, R.H. (Wiley, 1998)
In a single generation of selection, two lines of Glossina morsitans centralis were established that differed significantly in susceptibility to Trypanosoma congolense clone IL 1180. Reciprocal crosses demonstrated that susceptibility was a maternally inherited trait. Differences between the lines, to all phases of the trypanosome infection, were maintained for eight generations whereas differences in susceptibility to midgut infections were maintained for twenty-eight generations. Thereafter, the lines did not differ in susceptibility to Trypanosoma congolense IL 1180. Susceptibility to infections with Trypanosoma congolense IL 1180 was only a weak predictor of susceptibility to T. congolense clones IL 13-E3 and K60/1, as well as clone T. brucei brucei STIB 247-L. However, the susceptible and refractory lines displayed these phenotypes when tested with Trypanosoma vivax, indicating that the factors that affect susceptibility to trypanosomes are expressed both within and outside the midgut.